Grit Applied Within: Identity and Well-being. Issue 2 (3rd April 2019) - Weisskirch, Robert S.
ABSTRACT: This study investigates how grit, perseverance in the face of challenges and focus on achieving goals, relates to identity development and how identity development mediates the relationship between grit and well-being. Emerging adult college students (N = 232) indicated their grit, identity status, and well-being by completing an online questionnaire. Grit-perseverance of effort was associated with all identity statuses. Grit-consistency of interest was associated most identity statuses. Commitment and ruminative exploration mediated the relationship between grit and happiness and self-esteem, respectively.